2006
DOI: 10.1177/1032373206063110
|View full text |Cite
|
Sign up to set email alerts
|

Accounting at the boundaries of the sacred: the regulation of the Spanish brotherhoods in the eighteenth century

Abstract: Recently, accounting research on religious organizations has concentrated on the sacred/profane dichotomy. We analyse how dissimilar perceptions of the sacred led to different roles of accounting in sacred organizations and, consequently, to different behaviours in a process of accountability. We study the accountability process imposed after 1769 by Spanish Enlightenment governments upon the brotherhoods, secular institutions within the Catholic Church that were formed to conduct charitable activities and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Thirdly, this study contributes to the research on the relationship between accounting and religious institutions that still remains scant, according to Carmona and Ezzamel (2006) (with the notable exceptions of Swanson and Gardner, 1986;Faircloth, 1988;Llopis et al, 2002;Fonfeder et al, 2003;Álvarez-Dardet Espejo et al, 2006;Cordey, 2006;Prieto et al, 2006;Dobie, 2008Dobie, , 2011. This study is focused on the Papal States that were one of the most important religious institutions in the world.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Thirdly, this study contributes to the research on the relationship between accounting and religious institutions that still remains scant, according to Carmona and Ezzamel (2006) (with the notable exceptions of Swanson and Gardner, 1986;Faircloth, 1988;Llopis et al, 2002;Fonfeder et al, 2003;Álvarez-Dardet Espejo et al, 2006;Cordey, 2006;Prieto et al, 2006;Dobie, 2008Dobie, , 2011. This study is focused on the Papal States that were one of the most important religious institutions in the world.…”
Section: Resultsmentioning
confidence: 95%
“…The second category, instead, consists of all the studies that have explored accounting and its development in religious institutions (e.g. Swanson and Gardner, 1986;Faircloth, 1988;Llopis et al, 2002;Fonfender et al, 2003;Álvarez-Dardet Espejo et al, 2006;Cordery, 2006;Prieto et al, 2006;Dobie, 2008Dobie, , 2011. This study contributes to the second stream of research.…”
Section: Notesmentioning
confidence: 99%
“…In particular, Hazelrigg (1969) has observed that, by definition, empirical research in 'secret' organisations is scarce, but the transition of this organisation to the public sector facilitated research access and this study adds to our understanding of accounting in a 'secret' organisation. This paper also has four wider implications: (1) it underlines the need for contextual studies of accounting information (Broadbent & Guthrie, 2008;Miller, 1994), (2) it extends our understanding of the nature of voluntary organisations: it adds further scepticism over the 'sacred/secular divide' (Bigoni et al, 2013;Booth, 1993;Laughlin, 1988) and addresses the complexity of religious non profit organisations (Espejo et al, 2006;Jacobs, 2005) by introducing the concept of secrecy, (3) this study also contributes to our understanding of clinical receptivity to accounting information, and (4) most importantly, this study also demonstrates the need to extend the emergent theory of transparency in accounting to internal transparency (Heald, 2006a(Heald, , 2006b(Heald, , 2012Hood & Heald, 2006) in public sector accounting contexts. In particular Heald (2012) observes the importance of inwards transparency and this study supports this perspective.…”
Section: Resultsmentioning
confidence: 95%
“…La gestión de este tipo de organizaciones es importante por la necesidad de rendir cuentas sobre el uso de los recursos de la misma y la honestidad de sus gestores. Además, José Horacio García y Sergio Martínez: La Contabilidad de la Real e Ilustre Cofradía de Nuestro Padre Jesús Nazareno de Cartagena durante el segundo tercio del Siglo XX __________________________________________________________________________________ 94 resulta de especial interés la dualidad entre lo sacro y lo profano de la contabilidad al tratarse de instituciones seculares dentro de la Iglesia Católica cuyo papel en la sociedad y sus actividades caritativas son considerados por muchos de sus hermanos como una forma de acercarse a la vida sacra (Álvarez-Dardet et al, 2006). Importantes aportaciones a este objeto de estudio son los trabajos de López-Manjón et al (2012) y Álvarez-Dardet et al (2006) centrados en el estudio del papel de la contabilidad en la Cofradías españolas en los siglos dieciséis y dieciocho, respectivamente.…”
Section: Introductionunclassified
“…Además, José Horacio García y Sergio Martínez: La Contabilidad de la Real e Ilustre Cofradía de Nuestro Padre Jesús Nazareno de Cartagena durante el segundo tercio del Siglo XX __________________________________________________________________________________ 94 resulta de especial interés la dualidad entre lo sacro y lo profano de la contabilidad al tratarse de instituciones seculares dentro de la Iglesia Católica cuyo papel en la sociedad y sus actividades caritativas son considerados por muchos de sus hermanos como una forma de acercarse a la vida sacra (Álvarez-Dardet et al, 2006). Importantes aportaciones a este objeto de estudio son los trabajos de López-Manjón et al (2012) y Álvarez-Dardet et al (2006) centrados en el estudio del papel de la contabilidad en la Cofradías españolas en los siglos dieciséis y dieciocho, respectivamente. Estos autores destacan el hecho de que el papel de la contabilidad depende, no tanto del sistema de creencias establecido sino de la percepción de sus miembros respecto de la contabilidad, y que, si bien se asocia a la esfera de lo profano, su utilización para el control de las actividades depende de la diferencia en la percepción de los límites entre lo sacro y lo profano.…”
Section: Introductionunclassified